(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In this article, we provide information about the stages of development of the electric car industry through the data we know and do not know about the world electric car industry today, as well as statistics. We hope that in the future the results of this data and research will be used for the electric car industry of Uzbekistan